2001
DOI: 10.1016/s0736-5748(01)00025-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinase signalling in oligodendrocytes: a comparison of primary cultures and CG‐4

Abstract: Oligodendrocytes play a significant role in the central nervous system, as these cells are responsible for myelinating axons and allowing for the efficient conduction of nerve impulses. Therefore, any understanding we can gain about the functional biology of oligodendrocytes will give us important insights into demyelinating diseases such as multiple sclerosis, where oligodendrocytes and myelin are damaged or destroyed. Currently, much attention has focussed on the role of a family of mitogen-activated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 87 publications
3
22
0
Order By: Relevance
“…It has previously been shown that the inactivation of ERKs together with the activation of JNK and/or p38 may be critical for apoptosis, and an increase in ERK activity has been correlated to the increased survival of CG-4 cells differentiated into oligodendrocytic cells (29) and neuronal cell survival (82), whereas an increase of JNK or p38 activity may trigger apoptosis (82). Mitogen withdrawal that induces differentiation of CG-4 into multipolar oligodendrocytic cells, at an early (30-min) stage, is associated with a reduction of CREB and p44/42 MAPK (ERK1/2) phosphorylation (48,72). We observed an inhibition of ERK activity by agnoprotein at late stages (4 days) of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that the inactivation of ERKs together with the activation of JNK and/or p38 may be critical for apoptosis, and an increase in ERK activity has been correlated to the increased survival of CG-4 cells differentiated into oligodendrocytic cells (29) and neuronal cell survival (82), whereas an increase of JNK or p38 activity may trigger apoptosis (82). Mitogen withdrawal that induces differentiation of CG-4 into multipolar oligodendrocytic cells, at an early (30-min) stage, is associated with a reduction of CREB and p44/42 MAPK (ERK1/2) phosphorylation (48,72). We observed an inhibition of ERK activity by agnoprotein at late stages (4 days) of differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…progenitor cells (Stariha and Kim, 2001). When the CG-4 cell line was first established, it was cultured in the conditioned medium generated from the culture of neuroblastoma B104 cells.…”
Section: Hypothesismentioning
confidence: 99%
“…CG-4 cells began to show morphological characteristics of mature oligodendrocytes within two days when maintained in the differentiation medium (Stariha and Kim, 2001).…”
Section: Conditioned Medium Of B104 Cell Culturementioning
confidence: 99%
See 2 more Smart Citations